2005
DOI: 10.1111/j.1365-3016.2005.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term paracetamol therapy during pregnancy and a lower rate of preterm birth

Abstract: The relationships between short-term oral paracetamol treatment during pregnancy and mean gestational age and birthweight, in addition to the prevalence of preterm birth and low birthweight were estimated using newborn infants in the population-based large dataset of the Hungarian Case-Control Surveillance of Congenital Abnormalities between 1980 and 1996. Gestational age and birthweight were medically recorded. Of 38 151 newborn infants, 173 were born to mothers who had paracetamol treatment during pregnancy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…Acetaminophen use during pregnancy was not associated with a change in the risk of miscarriage, LBW or SGA. In contrast to previous reports, 5,6 we found no reduced risk of stillbirth or of preterm birth among pregnancies with acetaminophen exposure. However, our results are based on a large population-based study and included both over-the-counter and prescribed medication.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Acetaminophen use during pregnancy was not associated with a change in the risk of miscarriage, LBW or SGA. In contrast to previous reports, 5,6 we found no reduced risk of stillbirth or of preterm birth among pregnancies with acetaminophen exposure. However, our results are based on a large population-based study and included both over-the-counter and prescribed medication.…”
Section: Discussioncontrasting
confidence: 99%
“…8 Inhibition of Prostacyclin (PGI 2 ) synthesis and an imbalance between PGI 2 (a vasodilator) and Thromboxane A2 (TXA 2 , a vasoconstrictor) have been suggested as an explanation for these associations. 6,8 In contrast, a reduction in PGI 2 synthesis could also be associated with an increased risk of pre-eclampsia, 9 leading to an increased risk of induced preterm birth which would not be detected in a study using only spontaneous preterm births as endpoints. Induced preterm delivery occurs in 15-25% of all preterm births, with hypertensive disorders as the major proximal cause.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Remarkably, a retrospective Hungarian study reported an identical increase in mean gestational age of infants exposed to paracetamol during pregnancy (2.8 days), with a significant reduction in preterm deliveries (3.5% versus 9.2%), although they did not distinguish between male and female offspring (Czeizel et al ., 2005). The authors speculated that paracetamol may prolong pregnancy via a reduction in prostacyclin synthesis, consistent with findings from a randomised controlled trial showing that low-dose aspirin (another COX inhibitor) also reduced preterm delivery (CLASP (Collaborative Low-dose Aspirin Study in Pregnancy) Collaborative Group, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…One of the suggested explanation for this association is inhibition of Prostacyclin (PGI2) synthesis and inequality between PGI2 (a vasodilator) and Thromboxane A2 (TXA2, a vasoconstrictor) [8,9]. Similarly, a reduction in PGI2 synthesis could also be coupled with an augmented risk of pre-eclampsia leading to an amplified risk induced preterm birth that could not be detected in a study using only spontaneous preterm births as endpoints [10].…”
Section: Acetaminophen and Preterm Birthmentioning
confidence: 99%